(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to know the effect of using the Sketch pad program on mathematics achievement and higher thinking skills among students of the Technical Institute, and in order to achieve the objectives of the research, the researchers adopted the experimental design with a post-test for higher thinking skills. The experiment was achieved by testing (64) students of the first stage in the Survey Techniques Department at the Technical Institute / Baquba. The experimental group (30) students studied using the Sketch pad program and the control group (34) students planned to study mathematics according to the usual method. Previous achievement - previous knowledge - (Udel Daniles) test for intelligence, the scientific material and behavioral goals were determined according to Bloom’s cognitive levels and the preparation of teaching plans for the two research groups as well as the higher thinking skills test which consists of (25) paragraphs of two types (objective and essays) distributed on ( 5) Skills (analysis - synthesis - evaluation - creative thinking - critical thinking), and by using the appropriate statistical methods and the SPSS program, the results reached the existence of statistically significant differences at the level of (0.05) In favor of the experimental group.